Hubungan Tingkat pengetahuan dan Sikap dengan Praktik Pencegahan COVID-19 pada Masyarakat Pengguna Internet di Kota Semarang - Dwi Sutiningsih (Jurnal Epidemiologi Kesehatan Komunitas, 2021)
Background: The city of Semarang was ranked first in the highest confirmed case of COVID-19 in Central Java. Various control efforts have been made to stop the spread of this disease through government regulations and behavioral interventions in the community that depend on the compliance of the community itself. This study aims to analyze the level of health literacy, level of knowledge, attitudes and prevention practices related to COVID-19 in the general public of Semarang City.Methods: This study uses an observational analytic method with a cross-sectional approach which is carried out on the people of Semarang City. Data was collected through a google form questionnaire which was distributed online through social media from October 12 to November 9, 2020 and managed to collect 407 respondents from 16 sub-districts in Semarang City. The questionnaire consists of 42 questions covering the level of knowledge, attitudes and practices of prevention against COVID-19. Data were analyzed by univariate and bivariate with Chi-square statistical analysis.Result: The knowledge of internet users in Semarang City regarding COVID-19 was mostly good (50.1%), the attitudes and practices of preventing COVID-19 were also mostly good (56.5% and 50.6%). There was a significant relationship between the level of knowledge about COVID-19 and COVID-19 prevention practices (p-value=0,001). There was a relationship between attitudes related to COVID-19 and COVID-19 prevention practices (p-value=0.001).Conclusion : There is a relationship between the level of knowledge and attitudes towards COVID-19 prevention practices in the internet user community in Semarang City. Improved health education is needed to improve literacy and prevention practices for COVID-19.